Vida Saludable: Entendiendo la etiqueta de datos nutricionales - Karla P. Shelnutt (EDIS)
FCS8883-Span, a 2-page fact sheet by Karla P. Shelnutt, is the Spanish language version of FCS8883/FY1127 Healthy Eating: Understanding the Nutrition Facts Label. It explains the nutrition facts label — why it is needed and how to read it. Published by the UF Department of Family Youth and Community Sciences, November 2009.